Artificial Oxygen Carrier Its Frontline - Kobayashi, K.; Kobayashi, K.; Tsuchida, E.; Tsuchida, E.; Horinouchi, Hirohisa.; Horinouchi, Hirohisa. (Keio University International Symposia for Life Sciences and Medicine ;, 2005)
This volume of the Keio University International Symposia for Life Sciences and Medicine contains the proceedings of the 13th symposium held under the sponsorship of the Keio University Medical Science Fund. The fund was est- lished by the generous donation of the late Dr. Mitsunada Sakaguchi. The Keio University International Symposia for Life Sciences and Medicine constitute one of the core activities sponsored by the fund,of which the objective is to contribute to the international community by developing human resources, promoting scienti?c knowledge, and encouraging mutual exchange. Each year, the Committee of the International Symposia for Life Sciences and Medicine selects the most signi?cant symposium topics from applications received from the Keio medical community. The publication of the proce- ings is intended to publicize and distribute the information arising from the lively discussions of the most exciting and current issues presented during the symposium. On behalf of the Committee, I am most grateful to the late Dr. Sakaguchi, who made the series of symposia possible. We are also grateful to the prominent speakers for their contribution to this volume. In addition, we would like to acknowledge the ef?cient organizational work performed by the members of the program committee and the staff of the fund. Naoki Aikawa, M. D. , D. M. Sc. , F. A. C. S.